2009
DOI: 10.1002/dvg.20497
|View full text |Cite
|
Sign up to set email alerts
|

IL7‐hCD25 and IL7‐Cre BAC transgenic mouse lines: New tools for analysis of IL‐7 expressing cells

Abstract: Summary: IL-7 is a cytokine that is required for T-cell development and homeostasis as well as for lymph node organogenesis. Despite the importance of IL-7 in the immune system and its potential therapeutic relevance, questions remain regarding the sites of IL-7 synthesis, specific cell types involved and molecular mechanisms regulating IL-7 expression. To address these issues, we generated two bacterial artificial chromosome (BAC) transgenic mouse lines in which IL-7 regulatory elements drive expression of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
67
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 30 publications
3
67
0
Order By: Relevance
“…In these mice [22], the pattern of transgene expression was similar to our IL-7GCDL mouse. However, an unresolved issue remains why hCD25 mRNA is expressed at higher levels than IL-7 mRNA in the liver [22]. In contrast, our IL-7GCDL mouse shows hardly any luciferase activity in the liver, which is in agreement with a recent report showing that steady-state IL-7 production in the liver is low [8].…”
Section: Il-7supporting
confidence: 63%
See 2 more Smart Citations
“…In these mice [22], the pattern of transgene expression was similar to our IL-7GCDL mouse. However, an unresolved issue remains why hCD25 mRNA is expressed at higher levels than IL-7 mRNA in the liver [22]. In contrast, our IL-7GCDL mouse shows hardly any luciferase activity in the liver, which is in agreement with a recent report showing that steady-state IL-7 production in the liver is low [8].…”
Section: Il-7supporting
confidence: 63%
“…These observations suggest that fluorescent proteins are not suitable to reliably visualize the relatively weak activity of the Il7 promoter. However, this sensitivity problem was overcome by two other BAC-transgenic IL-7 reporter mice, expressing either hCD25 or Cre instead of fluorescent proteins [22]. In these mice [22], the pattern of transgene expression was similar to our IL-7GCDL mouse.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Several reports, including our own, have shown that IL-7 is predominantly produced by TECs within the thymus (13)(14)(15)(16). Using IL-7 reporter transgenic mice, in which YFP expression identifies a subset of TECs that coexpress high levels of Il7 (referred to as Il7 YFP+ TECs), we documented that Il7 YFP+ TECs gradually decay with age in a thymocyte-dependent manner that correlated inversely with the emergence of CD80-expressing mTECs, suggesting that these cells may define a particular cortical epithelial subset.…”
mentioning
confidence: 77%
“…Like other related cytokines (IL-2, IL-4, IL-9, IL-15, and IL-21), IL-7 is a member of the so-called common g-chain (g c ) family (2). It is produced by many different stromal cell types, including epithelial cells of the thymus and the intestine (3)(4)(5). The receptor for IL-7 consists of a heterodimer, the IL7Ra-chain, and the g c ; the IL-7Ra-chain is also part of the receptor for the thymic stromal lymphopoietin (TSLP) cytokine, and g c is also a component of other cytokine receptors (2).…”
mentioning
confidence: 99%